2020
DOI: 10.1097/md.0000000000023057
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric solid organ injury – frequency of abdominal imaging is determined by the treating department

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…This could aid in monitoring posttraumatic organ damage, and thus potentially avoid the overload of the need for CT scans, particularly in children after AT caused by external trauma or maltreatment. 38 As a limitation of the study, we only investigated male mice, even though some gender differences after blunt AT are likely and have been reported in rats during the development of an abdominal compartment syndrome. 39 Future studies need to also address the organ response in female mice.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This could aid in monitoring posttraumatic organ damage, and thus potentially avoid the overload of the need for CT scans, particularly in children after AT caused by external trauma or maltreatment. 38 As a limitation of the study, we only investigated male mice, even though some gender differences after blunt AT are likely and have been reported in rats during the development of an abdominal compartment syndrome. 39 Future studies need to also address the organ response in female mice.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies using this blunt AT model should not only define additional DAMPs, including mitochondrial debris, 36,37 but also whether damage markers such as L‐FABP and intestinal‐fatty acid binding protein could reliably discriminate the damaged organs with a sufficient spatial resolution. This could aid in monitoring posttraumatic organ damage, and thus potentially avoid the overload of the need for CT scans, particularly in children after AT caused by external trauma or maltreatment 38 …”
Section: Discussionmentioning
confidence: 99%
“…Consequently, one strength of this study is the large study population we were able to analyze. Many studies have demonstrated the ability of claims data to adequately represent pediatric care conditions [ 12 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…This represents a further advantage of specialized pediatric trauma care. Medical professionals who provide care to children daily might be more conscious of the potential long-term effects of radiation exposure, including the increased risk of cancer-related deaths [ 12 , 13 ]. In addition, pediatric departments typically cooperate with pediatric radiologists who ensure that radiation exposure is kept to a minimum [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation